DIALECTICAL BEHAVIOUR THERAPY FOR CSA-RELATED PTSD AMONG YOUNG ADOLESCENTS: A SINGLE CASE STUDY - Nazir, Sadaf; Syeda Farhana Kazmi (Journal of Ayub Medical College Abbottabad, 2023)
Childhood sexual abuse (CSA) is a pervasive and traumatic experience that can lead to long-lasting and profound psychological costs, especially post-traumatic stress disorder (PTSD) among young adolescents. This single case study explores the application of Dialectical Behaviour Therapy (DBT) as ground-breaking therapeutic approach for the treatment of child sexual abuse related PTSD in this vulnerable population. DBT found to be effective for treating CSA related PTSD, according to a growing body of research. This case study presents the course of treatment of 13 years old girl with CSA-related PTSD who received Dialectical Behaviour Therapy as treatment. In this instance, the client reacted to the therapy and displayed positive changes. Following the treatment, the client’s PTSD criteria were no longer met, evidenced by substantial drops on the scale used for evaluation. The article discusses the treatment implications of DBT and how well it treats children with PTSD related to CSA.